Pharmacological Uses and Health Benefits of Ginger (Zingiber officinale) in Traditional Asian and Ancient Chinese Medicine, and Modern Practice - Mohamad Hesam SHAHRAJABIAN; Wenli SUN; Qi CHENG (Notulae Scientia Biologicae, 2019)
Ginger (Zingiber officinale) has been used as a spice and a medicine for over 200 years in traditional Chinese medicine. Ginger is an important plant with several medicinal and nutritional values used in Asian and Chinese tradition medicine. Ginger and its general compounds such as Fe, Mg, Ca, vitamin C, flavonoids, phenolic compounds (gingerdiol, gingerol, gingerdione and shogaols), sesquiterpenes, paradols has long been used as an herbal medicine to treat various symptoms including vomiting, pain, cold symptoms and it has been shown to have anti-inflammatory, anti-apoptotic, anti-tumor activities, anti-pyretic, anti-platelet, anti-tumourigenic, anti-hyperglycaemic, antioxidant anti-diabetic, anti-clotting and analgesic properties, cardiotonic, cytotoxic. It has been widely used for arthritis, cramps, sprains, sore throats, rheumatism, muscular aches, pains, vomiting, constipation, indigestion, hypertension, dementia, fever and infectious diseases. Ginger leaves have also been used for food flavouring and Asian traditional medicine especially in China. Ginger oil also used as food flavouring agent in soft drink, as spices in bakery products, in confectionary items, pickles, sauces and as a preservatives. Ginger is available in three forms, namely fresh root ginger, preserved ginger and dried ginger. The pharmacological activities of ginger were mainly attributed to its active phytocompounds 6-gingerol, 6-shogaol, zingerone beside other phenolics and flavonoids. Gingerol and shogaol in particular, is known to have anti-oxidant and anti-inflammatory properties. In both traditional Chinese medicine, and modern China, Ginger is used in about half of all herbal prescriptions. Traditional medicinal plants are often cheaper, locally available and easily consumable raw and as simple medicinal preparations. The obtained findings suggest potential of ginger extract as an additive in the food and pharmaceutical industries.